Vorstellungen von Lehramtsstudierenden zum Grenzwertbegriff (mathematica didactica, 2022)
Reliable ideas about deep mathematical concepts of mathematics teachers are an indispensable prerequisite for high-quality mathematics lessons that are also meaningful for the students. There are several (normative) basic ideas (“Grundvorstellungen”) for certain mathematical concepts, which illuminate different facets of the mathematical concept in question. In this article, didactic concepts of ideas of learners are discussed and applied to the concept of the limit of sequences. For this purpose, an empirical study is presented, which collects and classifies student teachers’ written formulations before and after an intervention (attendance of a didactically oriented analysis course). It turns out that explicitly addressing normative basic ideas (“Grundvorstellungen”) leads to a significant (albeit small) increase in quality in terms of this concept.